2022
DOI: 10.1007/s12015-022-10350-y
|View full text |Cite
|
Sign up to set email alerts
|

The miR151 and miR5100 Transfected Bone Marrow Stromal Cells Increase Myoblast Fusion in IGFBP2 Dependent Manner

Abstract: Background Bone marrow stromal cells (BMSCs) form a perivascular cell population in the bone marrow. These cells do not present naïve myogenic potential. However, their myogenic identity could be induced experimentally in vitro or in vivo. In vivo, after transplantation into injured muscle, BMSCs rarely fused with myofibers. However, BMSC participation in myofiber reconstruction increased if they were modified by NICD or PAX3 overexpression. Nevertheless, BMSCs paracrine function could play a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Furthermore, it was shown that they can fuse with myoblasts and incorporate into newly formed myofibers, although to a very limited extent [ 33 ]. In mice, it was also shown that the myogenic potential of BMSCs, defined as the ability to convert into myogenic cells, can be promoted by overexpression of genes encoding NICD (Notch Intracellular Domain), β-CATENIN, PAX3 or miRNAs involved in muscle regeneration [ 34 , 35 ]. Despite the limited naïve myogenic potential, BMSCs are still considered in terms of therapy for dysfunctional muscles due to their other properties, that is as immunomodulatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that they can fuse with myoblasts and incorporate into newly formed myofibers, although to a very limited extent [ 33 ]. In mice, it was also shown that the myogenic potential of BMSCs, defined as the ability to convert into myogenic cells, can be promoted by overexpression of genes encoding NICD (Notch Intracellular Domain), β-CATENIN, PAX3 or miRNAs involved in muscle regeneration [ 34 , 35 ]. Despite the limited naïve myogenic potential, BMSCs are still considered in terms of therapy for dysfunctional muscles due to their other properties, that is as immunomodulatory agents.…”
Section: Discussionmentioning
confidence: 99%